Analisis Visualisasi Data Game Online RMT (Real Money Trading) di Indonesia Dengan Metode Business Intelligence Menggunakan Dashboard Tableau - Rizky Ramdhani; Rahmi Imanda (LPPM STIKOM Tunas Bangsa, 2024)
This research analyzes the trend of RMT (real money trading) online games in Indonesia in terms of average active players and game popularity. This research uses raw online game data in terms of the average number of active players and data on the number of RMT game trends in Indonesia according to Google Trends. Temporal analysis and business intelligence methods are used to analyze data and produce data visualizations. The research results show that the Riau Islands and Jakarta are the regions with the highest RMT activity trends in Indonesia. The Riau Islands occupy the highest position in the MMORPG and Sandbox genres, while Jakarta occupies the highest position in the ARPG and Mix genres. East Nusa Tenggara is the region that has the lowest RMT activity trend in Indonesia. East Nusa Tenggara occupies the lowest position in the four game genres that are the object of this research. The relationship between data on active players in the world and the trend or popularity of RMT online games in Indonesia shows that the Riau Islands and Jakarta are claimed to contribute the highest percentage of active players throughout the world in several RMT online games which are the object of this research in Indonesia.